Dermatological And Allergy Approach To A Dog Population From A Veterinary Consultation At The Tropical Coastal City Of São Paulo, Brazil - Campos, Isabela (2019)
Background: Dermatological problems are between the major reasons for dog veterinary consultation, with allergic pruritic conditions playing a relevant and increasing role. Besides genetic predisposition associated with sensitization and skin barrier imbalance, indoor/outdoor life is also associated with different level of exposure to several airborne allergens. Food allergy is also a known condition requiring clinical and food trials for specific diagnosis. Itch is a common sign associated to pruritic conditions like atopic or food allergy dermatitis, resulting in frequent skin infections. Diversity and concentration of airborne allergens as well as skin barrier condition may in turn vary according to environmental conditions, influencing the pattern of sensitization and allergy. Hence, this study aimed to identify the patterns of skin allergy in dogs of the city of São Paulo, Brazil, a highly populated tropical coastal area. Methods: An 84 mostly allergic dog patient population (45 males and 39 females) attending the Pompeia Veterinary Hospital outpatient consultation was selected from 2015 to 2017 by clinical evaluation and submitted to food allergy restriction measures. Thirty one patients (36.9%) belonged to predisposed breeds, 77.4% were indoor and 22.6% outdoor. Results: First signs started from the age of 2 months to 11 years old. Several comorbidities were found in 23.5% of the 1-3 years old group and in 29% of the above group. Atopic dermatitis (AD) was diagnosed in 69% of the patients and food allergy (FA) in 4.8%, but no simultaneous AD+FA was found. Malassezia overgrowth (MO) was diagnosed in 58.3% of the patients, half of them, including 5 from predisposed breeds, lacking a diagnosis of allergy. Flea allergy dermatitis was diagnosed in only one patient with no AD nor FA, but presenting MO. Bacterial otitis was observed in 6% of the patients, either with AD or AD+MO. Malassezia overgrowth correlated positively with outdoor living (p=0.009) but negatively with AD. Food allergy correlated positively with an increasing age at the onset of signs (p=0.01). Conclusion: Although roughly one-third of AD-patients presented with MO, this has been frequently observed as the only diagnosed cause of dermatitis, associated with outdoor living, which could be probably related to the local perennial warm and wet climate. The FA onset of signs associated with a higher age should follow further investigation regarding the implicated food.